Sub‐arctic river bank dynamics and driving processes during the open‐channel flow period. Issue 5 (11th February 2020) - Lotsari, E.; Hackney, C.; Salmela, J.; Kasvi, E.; Kemp, J.; Alho, P.; Darby, S.E.
Abstract: There is growing concern that rapidly changing climate in high latitudes may generate significant geomorphological changes that could mobilise floodplain sediments and carbon; however detailed investigations into the bank erosion process regimes of high latitude rivers remain lacking. Here we employ a combination of thermal and RGB colour time‐lapse photos in concert with water level, flow characteristics, bank sediment moisture and temperature, and topographical data to analyse river bank dynamics during the open‐channel flow period (the period from the rise of the spring snowmelt flood until the autumn low flow period) for a subarctic river in northern Finland (Pulmanki River). We show how variations of bank sediment temperature and moisture affect bank erosion rates and locations, how bank collapses relate to fluvial processes, and elucidate the seasonal variations and interlinkages between the different driving processes. We find that areas with high levels of groundwater content and loose sand layers were the most prone areas for bank erosion. Groundwater seeping caused continuous erosion throughout the study period, whereas erosion by flowing river water occurred during the peak of snowmelt flood. However, erosion also occurred during the falling phase of the spring flood, mainly due to mass failures. The rising phase of the spring flood therefore did not affect the river bank as much as its peak or receding phases. This is explained because the bank is resistant to erosion due to the prevalence of still frozen and drier sediments at the beginning of the spring flood. Overall, most bank erosion and deposition occurrences were observed during the low flow period after the spring flood. This highlights that spring melt, while often delivering the highest discharges, may not be the main driver of bank erosion in sub‐arctic meandering rivers. © 2019 John Wiley & Sons, Ltd. Abstract : Groundwater seeping caused continuous erosion throughout the study period, whereas erosion by flowing river water occurred during the peak of snowmelt flood. Overall, most bank erosion and deposition occurrences were observed during the low flow period after the spring flood. The spring melt, while often delivering the highest discharges, may not be the main driver of bank erosion in subarctic meandering rivers.